Use of Biological Disease-Modifying Antirheumatic Drugs (bDMARD) Therapy in Rheumatoid Arthritis: A Review of Side Effects and Immunological Mechanisms: English - Jody Yusuf; Rofiq, Ainur; Sofyansyah Hermaya, Aditya; Dian Islami, M (Asian Multidisciplinary Research Journal of Economy and Learning, 2024)
Rheumatoid arthritis (AR) is a chronic autoimmune disease that causes symmetrical inflammation of small and large joints and other organs. AR treatment has evolved with the introduction of Biological Disease-Modifying Antirheumatic Drugs (bDMARD) that target specific immunological pathways in AR pathogenesis thereby increasing the effectiveness of therapy. The study aims to review the side effects of bDMARD and its immunological mechanisms. The method used was a literature review by searching for articles from scientific databases related to the side effects and immunological mechanisms of bDMARD in AR. Results suggest that bDMARD are effective in controlling inflammation and preventing joint damage, but have significant side effects, including an increased risk of serious infections such as tuberculosis reactivation and opportunistic infections such as shingles. In addition, there is a risk of malignancy, major cardiovascular events (MACE), gastrointestinal disorders, and hematological disorders such as neutropenia. The immunological mechanism of bDMARD involves inhibition of pro-inflammatory cytokines such as TNF-α and IL-6, as well as suppression of T cell activation and B cells that play a role in AR inflammation. In conclusion, although bDMARD provide significant therapeutic benefits in AR treatment, monitoring side effects ensures long-term safety.